Factors Associated With African Animal Trypanosome Infection In Cattle In Kiang West District, Lower River Region, The Gambia - Sanyang, K. (University Of Ghana, 2021)
Background: African Animal Trypanosome (AAT) infection is caused by hemoparasites (Trypanosomes) that are transmitted by the Tsetse fly. In the Gambia, cattle production produces the highest livestock output that contributes 54% to the total agricultural GDP which accounts for 34 % of National Gross Domestic Productivity (GDP). However, diseases including AAT infection cause huge losses to cattle production with 53.4% deaths annually. This study determined the prevalence of risk factors associated with AAT infection in cattle in Kiang West District, The Gambia. Methods A cross-sectional study involving a sample size of 384 cattle from four randomly selected villages of Kiang West District was conducted from February 2020 to June 2021. Blood samples collected were screened for AAT infection using buffy coat and Giemsa staining methods. Data on animal demographic and husbandry factors were collected using a structured questionnaire and statistically analysed using univariate and multivariate logistic regression techniques. Results: The overall prevalence of AAT infection was 11.7% (45/384), of which 57.78% (26/45) were Trypanosome vivax, 24.40% (11/45) were Trypanosome congolense and 4.44% (2 /45) were Trypanosome brucei. Mix-infection (T. congolense and T. vivax) was 33.33% (6/45). Among the study villages, Jifarong had 33.3% (15/45) AAT infections. A total of 29.95% (115/384) of cattle had anaemia. AAT infection was significantly associated with crossbreed [aOR=11.9 ;95% CI: 1.87-74.85] and anaemia [aOR= 2.0; 95% CI: 1.07 – 3.89]. The age and sex of cattle were not associated with AAT infection. Conclusion: There is a high prevalence of AAT infection in Kiang West District Lower River Region, The Gambia and Trypanosome vivax was found to be the most dominant species among causing infection in cattle. Crossbreed cattle and anaemia condition were found the associated risk factors to AAT in cattle. To minimize the burden of AAT on cattle production in the Gambia, we recommend farmers adopt the raring of trypanotolerant breeds (Ndama) of cattle and implement husbandry practices that lessen anaemia in cattle
MPhil. Applied Epidemiology And Disease Control
Keywords: African Animal Trypanosome Infection; Kiang West District; Lower River Region; The Gambia